"Confidential Letter to all Commanding officer of Sub-Post in Jurisdiction of Post of Arecibo" - Todd, Roberto H. (My University, 1898)
Medidas de Preventivas para disturbios en la temporada navideña.
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.